Systolic blood pressure values might further risk-stratify the adverse outcomes of LVH in older patients with chronic kidney disease. Issue 1 (December 2016) - Franco Palacios, Carlos; Goyal, Pankaj; Thompson, Amanda; Deschaine, Brent
Abstract Background LVH is highly prevalent in patients with CKD and is independently associated with subsequent cardiovascular events. We hypothesized that adding systolic blood pressure values to LVH might differentiate different subgroups of patients at higher risk of cardiovascular events (CVE) and other adverse outcomes. Methods Retrospective cohort study of 243 patients older than 60 years with stages 1-5 pre-dialysis CKD. LVH was assessed by electrocardiogram or echocardiogram. Results Cardiovascular events occurred in 7 patients (10.3%) among those with SBP <130 and no LVH, 8 patients (10.5%) among those with SBP ≥130 and no LVH, 7 patients (21.2%) among those with SBP <130 and LVH and 25 patients (37.9%) among those with SBP ≥ 130 and LVH. On multivariate analyses, comparing to SBP < 130 and no LVH, the HR for CVE in those with SBP ≥ 130 and LVH was 4 (1.75, 10.3), p = 0.0007; 2.13 (0.71, 6.32)p = 0.16 in those with SBP <130 and LVH and 1.20 (0.42, 3.51)p = 0.72 in those with SBP ≥130 and no LVH. No significant differences were noted in changes in renal function and mortality rates among the groups. Conclusion The combination of higher systolic blood pressure and LVH might identify older patients with CKD at higher risk of cardiovascular outcomes.